FRI0646-HPR Does Painful Hand Arthritis Influence Motor Cortex Excitability and Motor Skill Learning?. (15th July 2016) - Parker, R.; Lewis, G.; Rice, D.; McNair, P.
Abstract : Background: Painful hand arthritis frequently leads to reduced quality of life [1] and impaired hand function [2]. This may be partially mediated by impaired motor control [3] and changes in primary motor cortex excitability [4]. Previous studies have shown that other chronic pain conditions are associated with reduced motor cortex inhibition [5], which is also associated with motor learning [6]. Therefore, impaired motor control and learning in arthritic pain populations is potentially due to changes in motor cortex excitability. Supporting this, previous studies have shown that motor learning may be influenced by acute experimental pain. However, no previous study has sought to establish whether chronic arthritic pain may influence motor learning and if this relates to changes in motor cortex excitability. Objectives: To provide a thorough analysis of corticomotor and intracortical excitability in people with painful hand arthritis, and to examine the relationship between these measures and performance on a motor skill learning task. Methods: Twenty three people with arthritic hand pain and 20 pain-free controls participated in a cross-sectional study. Hand pain and function were assessed using the AUSCAN osteoarthritis hand index. Transcranial magnetic stimulation was used to measure corticomotor and intracortical excitability of a finger muscle. Motor skill learning was assessed using a 30 minute training task involving the index finger of the same hand. Results: Compared with controls, participants with hand arthritis showed evidence of reduced intracortical inhibition and enhanced facilitation (p<0.05). However, overall corticomotor excitability was normal. Participants with arthritis were initially poorer at the motor skill task, but over the total training time performance was equivalent between groups. There were no associations found between measures of intracortical or corticomotor excitability and motor skill learning or hand function. Conclusions: This study provides novel evidence that hand arthritis is associated with reduced intracortical inhibition similar to other chronic pain populations. However, no relationship was observed between these cortical alterations and impaired function or skill learning. References: Dziedzic et al. Rheumatology. 2007:46:963–7. Allen et al. Arthritis Rheum. 2006:54:551–6. de Oliveira et al. J Hand Ther. 2011:24:345–55. Maihofner et al. Brain. 2007:130:2671–87. Lefaucheur et al. Neurology. 2006:67:1568–74. Smyth et al. Hum Mov Sci. 2010:29:618–30. Disclosure of Interest: None declared